Implementasi Musik dalam Misi Lintas Budaya pada Program Pengabdian Masyarakat STT Kristus Alfa Omega di Daegu, Busan, dan Jinju Korea Selatan - Yunatan Krisno Utomo; Gregorius Suwito; Rini Adiyati; Ricky Nelson (Institut Kristen Teologi Real Batam, 2026)
Globalization has intensified cross-cultural interactions, demanding contextual and adaptive mission approaches that transcend conventional methods. This community service (PkM) study examines the role of music as a cross-cultural mission medium in STT Kristus Alfa Omega's community service activities across Daegu, Busan, and Jinju, South Korea. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation analysis. Findings reveal that music significantly enhanced participant engagement, fostered more inclusive cross-cultural interactions, and generated positive emotional and social responses toward the Gospel message. The adaptation of local musical elements combined with bilingual performance strategies strengthened community acceptance and deepened relational trust across cultural boundaries. Furthermore, music functioned not merely as a communicative medium, but as a strategic missiological instrument for building intercultural relationships, increasing community participation, and facilitating the internalization of spiritual values. These findings affirm that a contextual, music-based community service model holds substantial potential for replication across diverse multicultural contexts, contributing meaningfully to the development of contextual missiology in East Asia. Keywords: cross-cultural mission; contextual missiology; music as mission medium; community engagement; intercultural spirituality Abstrak Globalisasi telah mengintensifkan interaksi lintas budaya, menuntut pendekatan misi yang kontekstual dan adaptif melampaui metode konvensional. Studi Pengabdian kepada Masyarakat (PkM) ini mengkaji peran musik sebagai media misi lintas budaya dalam kegiatan pengabdian masyarakat STT Kristus Alfa Omega di Daegu, Busan, dan Jinju, Korea Selatan. Dengan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan analisis dokumentasi. Temuan menunjukkan bahwa musik secara signifikan meningkatkan keterlibatan partisipan, memfasilitasi interaksi lintas budaya yang lebih inklusif, serta menghasilkan respons emosional dan sosial yang positif terhadap pesan Injil. Adaptasi elemen musik lokal yang dipadukan dengan strategi pertunjukan bilingual memperkuat penerimaan komunitas dan mempererat kepercayaan relasional lintas budaya. Lebih jauh, musik berfungsi bukan sekadar sebagai medium komunikatif, melainkan sebagai instrumen missiologis strategis dalam membangun relasi interkultural, meningkatkan partisipasi komunitas, dan memfasilitasi internalisasi nilai-nilai spiritual. Temuan ini menegaskan bahwa model PkM berbasis musik yang kontekstual memiliki potensi signifikan untuk direplikasi dalam berbagai konteks multikultural, berkontribusi pada pengembangan misiologi kontekstual di Asia Timur. Kata kunci: misi lintas budaya; misiologi kontekstual; musik sebagai media misi; keterlibatan komunitas; spiritualitas interkultural